Transformasi Digital dan Layanan Jarak Jauh Perpustakaan: Sebuah Narrative Literature Review - Intan Winda Oktavia; Larasati Zuhro Nur Faizah Surya Putri (Lembaga Yasin AlSys, 2026)
The acceleration of digital transformation requires educational and information services to adapt to the needs of digital society, including the provision of library access and services. This study aims to summarize, analyze, and compare previous research findings related to the transformation of digital library services. This study is a literature review using a comparative approach and a qualitative descriptive method. The research data sources consisted of scientific articles published in accredited national journals and several pieces of literature from academic repositories. The article search criteria included publications from 2018 to 2024 focusing on digital transformation, online services, or remote library services. Data were analyzed comparatively and descriptively to identify patterns of similarities and differences across studies and to determine general trends in the transformation of digital library services. The review results indicate that the implementation of digital library service transformation still shows uneven levels of readiness. The main challenges encountered include limited access to and infrastructure for technology, limited human resources, organizational and policy readiness, and user readiness. The strategies that need to be implemented include the provision of adequate internet networks, servers, and library information systems, the improvement of librarians’ competencies, the application of hybrid service models, and the development of collaborative activities and services with the government, communities, or other libraries. The conclusion of this study affirms that the transformation of library access and services is not merely a process of media conversion but a comprehensive change involving operational systems and management, organizational culture, and inter-institutional information relations and networks. These findings contribute to the development of digital library service studies and provide practical implications for strengthening governance, infrastructure, and librarians’ competencies in responding to the needs of digital-based information services.